Hemograma e mielograma de cães infectados experimentalmente com Rangelia vitalii - França, Raqueli Teresinha (2013)
Rangelia vitalii is a member of the protozoan phylum Apicomplexa, class Sporozoasida, order Piroplasmorida, that causes a disease called rangeliosis in dogs, popularly known as " bleeding plague" or "nambyuvú". The transmission of this parasite occurs through tick and affects dogs in rural and periurban areas especially in hotter times of the year, which favors an increase in ticks population. To date this disease has been described only in Brazil. Rangeliosis is characterized by anemia, jaundice, fever, splenomegaly, generalized lymph node enlargement, hemorrhage along the gastrointestinal tract, and persistent bleeding through the tips of the pinnae, external surface of the ears, nose, and oral cavity. The aim of this study was to evaluate hematologic changes and consequent bone marrow response during the acute phase in dogs experimentally infected with Rangelia vitalii. 12 dogs were, divided into two groups: group A consisted of five healthy animals, and group B consisted of seven dogs experimentally infected with R. vitalii. After inoculation, the animals were monitored for parasitemia by blood smears from the tips of the ear. In group B the parasite was found within erythrocytes, neutrophils and monocytes five days post-inoculation (PI). Blood samples with EDTA for complete blood count (CBC) were performed on days 0, 10, 20 and 30 PI and on days 10 to 20 PI the reticulocyte count. After blood collection, the dogs were anesthetized bone marrow aspiration for the myelogram. This study demonstrated a reduction (P <0.01) in erythrocyte count, hematocrit and hemoglobin in the infected group compared to control. On day 10 PI the infected animals showed a normocytic normochromic anemia, however, on day 20 PI was observed macrocytic hypochromic anemia and increased (P <0.05) in the red cell distribution width (RDW) in the infected group compared to control. A decreased (P <0.05) in total leukocyte count as a result of a decrease in neutrophil and eosinophil count was observed in the infected animals (P <0.05). In the infected group there was also an increase in lymphocyte and monocyte count in comparasion to control (P <0.05). Increased (P <0.01) in the reticulocyte count was observed in the infected group compared to the control group. The myelogram showed a decrease (P <0.05) in myeloid:erythroid ratio as a result of increased erythroid precursors (rubriblast, prorubricyte, rubricyte and metarubricyte) and a decrease in the myeloid lineage (myelocyte, band and segmented). Other cells such as lymphocytes, plasma cells and macrophages were more frequent in bone marrow on day 20 PI in the infected group compared to the control group. Our results, we conclude that rangeliosis can lead to a regenerative, immunomediated, hemolytic anemia, together with leukopenia due to neutropenia and eosinopenia, as well as lymphocytosis and monocytosis. These findings were observed in the acute phase experimental of infection and are similar to those found in cases of natural infection at different stages of the disease.